Efektivitas Integrasi Augmented Reality Dalam Pembelajaran Tematik Kelas 3 Siswa Sekolah Dasar Menggunakan Model ARCS - Kaharuddin Kaharuddin; Musliadi KH; Ilwan Syafrinal; Yonky Pernando (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The quality of education in Indonesia has become a serious problem in recent years. Various problems such as poor education management, inequality of facilities between urban and rural areas, and traditional learning methods that do not follow the development of modern technology make the quality of education low. This study aims to evaluate the effectiveness of the application of Augmented Reality (AR) in Theme 3 Thematic learning in Elementary Schools. The research method uses the MDLC (Multimedia Development Life Cycle) approach, with testing based on the ARCS (Attention, Relevance, Confidence, and Satisfaction) Motivation Model. In addition, a test of students' level of understanding was carried out using the Student Activity Sheet (LKPD). Data was obtained from 32 grade 3 elementary school students. The test results showed that the AR application had an excellent interpretation/very effective interpretation score of 86%, with details of 90% for Attention, 82% for Relevance, 81% for Confidence, and 84% for Satisfaction. The level of students' understanding of the material is also high, with an average score of 85. So it can be concluded that the Augmented Reality application is very feasible to be applied in the Theme 3 Thematic learning process in Elementary Schools because it is able to effectively increase students' interest and understanding.